Answer:
(-2,-6)
Explanation:
-9x +2y = 6
5x - 3y = 8
1) Make one of the coefficients the same - y.
-9x +2y = 6 * 3
5x - 3y = 8 * 3
-27x +6y = 18
10x - 6y = 16
2) Add the new equations.
(-27x +6y = 18) + (10x - 6y = 16)
(-27x +6y) + (10x - 6y) = 18 + 16
-17x = 34
3) Divide to find the value of x
-17x = 34
x = 34/-17
x = -2
4) Substitute x into either equation to find the value of y.
-9(-2) +2y = 6
18 +2y = 6
2y = -12
y = -12/2
y = -6
5(-2) - 3y = 8
-10 - 3y = 8
-3y = 18
y = 18/-3
y = -6
Your answer is (-2,-6).